This day in music an everyday record of musical facts - Cossar, Neil (Omnibus Press, 2014)
guide to the history of popular music-related events, especially rock music in the U.S. and U.K. Arranged by day, then by year, chiefly from the 1950s to 2009. Events noted include births, deaths, and marriages of musicians, number-one singles, arrests, drug busts, famous gigs, awards ceremonies, trivia about bands and music-industry celebrities, and more